Analisis Scaffolding Guru dalam Penerapan Computational Thinking di Kelas PAUD - Nila Kusumaningtyas; Joko Siswanto; Nur Latifah Dwi Mutiara Sari (CV. Creative Tugu Pena, 2026)
This study aims to analyze the forms of teacher scaffolding in the application of computational thinking in early childhood education. Computational thinking is a 21st-century skill that is important to develop from an early age through problem-solving activities, pattern recognition, abstraction, and the creation of simple algorithms. The success of implementing computational thinking in early childhood is greatly influenced by the teacher’s ability to provide scaffolding that aligns with the children’s learning needs. The study employs a qualitative approach with a case study design. The research participants consist of one classroom teacher as the primary subject and fifteen children aged 5–6 years involved in computational thinking-based learning activities. Additionally, one co-teacher was involved as a supporting informant to strengthen the data from observations and interviews. Data were collected through observation, in-depth interviews, and learning documentation. Data were collected through participatory observation, in-depth interviews, and learning documentation. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which includes data condensation, data presentation, and drawing conclusions. The research results indicate that teachers employ four primary forms of scaffolding: verbal scaffolding, demonstrative scaffolding, collaborative scaffolding, and reflective scaffolding. Verbal scaffolding is the most dominant form in helping children understand problems and develop problem-solving strategies. Demonstrative scaffolding is effective in clarifying simple algorithmic concepts, while collaborative scaffolding fosters pattern recognition skills through peer interaction. Additionally, reflective scaffolding helps children evaluate the thinking processes they have undertaken. These findings indicate that the application of structured scaffolding can optimally support the development of computational thinking skills in young children. This study recommends strengthening the pedagogical competencies of early childhood education teachers in designing and implementing scaffolding strategies based on computational thinking.